Positive airway pressure telehealth models and long-term therapy termination: a healthcare database analysis - Holger Woehrle; Christoph Schoebel; Joachim H. Ficker; Andrea Graml; Jürgen Schnepf; Ingo Fietze; Peter Young; Michael Arzt (ERJ Open Research, 2024)
Background Telemonitoring-guided interventions can improve short-term positive airway pressure (PAP) therapy adherence, but long-term effects are unknown. This study investigated long-term PAP therapy termination in patients with sleep apnoea managed with standard care, telemonitoring-guided proactive care or telemonitoring-guided proactive care + patient engagement tool. Methods German healthcare provider data were analysed retrospectively. Individuals aged 18–100 years who started PAP from 2014 to 2019 and had device type/interface data were included. Time-to-termination periods were analysed using Kaplan–Meier plots and Cox proportional hazards regression, adjusted for age, sex, insurance type, and device and mask type. Results The per-protocol population (valid telemonitoring data) included 104 612 individuals (71% male; 95% aged >40 years). Mean follow-up was 3.3±2.0 years. The overall therapy termination rate was significantly lower in the telemonitoring-guided proactive care group versus standard care (20% versus 27%; p<0.001), and even lower in the telemonitoring-guided care + patient engagement tool group (11%; p<0.001 versus other treatment groups). Adjusted risk of therapy termination was lower versus standard care (hazard ratio 0.76, 95% confidence interval 0.74–0.78; and 0.41 (0.38–0.44) for telemonitoring-guided proactive care alone + patient engagement). Age <50 or >59 years and use of a nasal pillows or full-face mask were significant predictors of therapy termination; male sex, use of telemonitoring-guided proactive care (± patient engagement) and private insurance were significantly associated with lower therapy termination rates. Conclusions Use of telemonitoring-guided proactive care and a patient engagement tool was associated with lower rates of PAP therapy termination.